Efektivitas Problem-Based Learning (PBL) dengan Digital dan Integrasi Budaya Lokal Madura Terhadap Literasi Sains Siswa Sekolah Dasar: Learning Model, PBL, Digital, Madurese Local Culture, Scientific Literacy - Sutrisno, Tri (STIT Fatahillah, 2025)
This study aims to investigate the effectiveness of problem-based learning (PBL) with digital and Madurese local cultural integration on the scientific literacy of elementary school students. This study is based on the low scientific literacy of Indonesian students and the limited contextual, innovative, and appropriate learning models for local cultural characteristics. This study uses a quantitative approach with a quasi-experimental design with a pretest-posttest control group type. The subjects were fifth-grade students at SDN Kalianget Barat III, Sumenep Regency, who were divided into two groups: an experimental group and a control group. The experimental group received learning using a digital media-based PBL model that raised the Madurese cultural context, such as Tanean Lanjhang and Rokat Tase, while the control group followed conventional learning. The research instruments were a scientific literacy test and a student response questionnaire. The analysis results showed that the average posttest score of the experimental group's scientific literacy (83.14) was significantly higher than the control group (66.79), with a significance value of p <0.05 based on an independent t-test. Furthermore, the questionnaire showed that 89.3% of students responded positively to the learning model used. This finding indicates that the developed learning model is capable of creating active, contextual, and meaningful learning, as well as supporting the implementation of the Independent Curriculum and strengthening the Pancasila Student Profile. Therefore, this model is recommended as an innovative alternative for science learning based on local culture